Estimation of population distribution function involving measurement error in the presence of non response. Issue 10 (18th May 2020) - Yaqub, Mazhar; Shabbir, Javid
Abstract: This article addresses the problem of estimating population distribution function for simple random sampling in the presence of non response and measurement error together. We suggest a general class of estimators for estimating the cumulative distribution function using the auxiliary information. The expressions for the bias and mean squared error are derived up to the first order of approximation. The performance of the proposed class of estimators is compared with considered estimators both theoretically and numerically. A real data set is used to support the theoretical findings.